Lateral sinus pericranii with internal jugular vein communication - Michael Teklehaimanot Abera; Miskir Gebremariam Waktola; Etsehiwot Demeke Debele (Radiology Case Reports, 2024)
An abnormal communication between the extra and intracranial venous structures in the head is called sinus pericranii. The condition usually involves the frontal superior sagittal sinus. Occurrence in the lateral scalp is an uncommon pattern. Its commonest manifestation is scalp swelling, which can be cosmetically unappealing. Radiologic findings play an important role in correctly diagnosing the condition and planning treatment. In this case report, we present the computed tomography findings of a 10-year-old male patient who presented with right scalp swelling. Postcontrast head and neck computerized tomography diagnosed a lateral sinus pericranii with an unusual location in the right scalp that also involves the ipsilateral internal jugular vein. Subsequently, a conservative treatment approach with close clinical follow-up was adopted.